MetE: a promising protective antigen for tuberculosis vaccine development - Almujri, Salem Salman; Stylianou, Elena; Nicastri, Annalisa; Satti, Iman; Korompis, Marcellus; Li, Shuailin; De Voss, Christopher J.; Polo Peralta Alvarez, Marco; Tanner, Rachel; Bettencourt, Paulo J. G.; Ternette, Nicola; McShane, Helen (Frontiers in Immunology, 2025)
IntroductionTuberculosis (TB), caused by Mycobacterium tuberculosis (MTB), remains a significant global health concern. The existing vaccine, Bacillus Calmette-Guérin (BCG), provides inconsistent protection, highlighting the pressing need for a more effective vaccine. We aimed to identify novel MTB antigens and assess their protective efficacy as TB vaccine candidates.MethodsUsing immunopeptidomics, we identified 64 and 80 unique mycobacterial antigens derived from BCG and MTB, respectively. We prioritised antigens based on HLA allele coverage through an immunoinformatics approach.ResultsThe candidates, hisD, metE, and mmpL12, delivered as DNA vaccines, were evaluated for efficacy in mice using the ex vivo Mycobacterial Growth Inhibition Assay (MGIA) and metE was identified as a promising candidate. In vivo murine MTB challenge experiments confirmed the protective efficacy conferred by metE when formulated as recombinant protein with AS01™ or AddaS03™ adjuvants, compared to the naïve group. The immunogenic profiles of metE formulated in the two different adjuvants differed, with metE-AS01™ inducing antigen-specific IFN-γ, TNF-α, IL-2, IL-17, IgG1 and IgG2a-c, while metE-AddaS03™ induced TNF-α, IL-2, IL-17, IL-4, IgM, IgG1, IgG2b.ConclusionOur findings highlight metE as a promising protective antigen for future TB vaccine development.